Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Unveiling Pakistan’s hydro-climatic shifts: trends and change-points in soil moisture and potential evapotranspiration across Pakistan’s climatic zones - Darakshan Naeem; Abdullah Taib; Muhammad Awais; Rizwan Aziz; Muhammad Zaman (Meteorology and Atmospheric Physics, 2026)

Statistical optimization of exopolysaccharides by indigenously isolated Lactobacillus strain under submerged fermentation - Madah Zahra Awan; Fouzia Tabssum; Muhammad Nadeem; Najeeb Ullah; Abid Sarwar; Neha Mazhar; Tariq Aziz; Ashwag Shami; Hanan Abdulrahman Sagini; Saleh A. Alsanie; Nouf Abdullah Alharbi; Mansour Albalji (World Journal of Microbiology and Biotechnology, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Effect of Different Application Rates and Types of Biochar on Soil Biochemical Characteristics and Greenhouse Gas Emissions - Muhammad Abdullah Aziz; Mosaed A. Majrashi (Journal of Soil Science and Plant Nutrition, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

Bamboo charcoal mitigates oxidised LDL-induced foam cell formation via molecular interaction and adsorption: Evidence from in silico and in vitro studies - Mutaman Hussein Abdullah; Ahmad Naqib Shuid; Mohd Yusmaidie Aziz; Muhammad Azrul Zabidi; Muhammad Mahyiddin Ramli; Rafeezul Mohamed (Chemistry and Physics of Lipids, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Revealing Lactiplantibacillus Plantarum K25 Derived (Z)-18-Octadec-9-Enolide in Modulating Aquaporin-8 in Colorectal Cancer by Bridging the Gut Microbiome and Membrane Biology - Tariq Aziz; Muhammad Aqib Shabbir; Abid Sarwar; Zhennai Yang; Lin Lin; Wafa Abdullah I. Al-Megrin; Ashwag Shami; Maher S. Alwethaynani; Areej A Alhhazmi; Fahad Al-Asmari; Fakhria A. Al-Joufi; Deema Fallatah (Cell Biochemistry and Biophysics, 2025)

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

Integrating MDT Tumor Board Shadowing into the Undergraduate Medical Curriculum: Perspective of Medical Students - Aasil Shayan Aziz; Masooma Shifa Rana; Salaar Ahmed; Muhammad Abdullah; Hafsa Khan Tareen; Ayesha Siddiq; Ahmed Nadeem Abbasi (Journal of Cancer Education, 2024)

Temporal characteristics of positive cloud-to-ground flashes from tropical thunderstorms - Muhammad Haziq Mohammad Sabri; Mohd Riduan Ahmad; Yuji Takayanagi; Shamsul Ammar Shamsul Baharin; Takeshi Morimoto; Zen-Ichiro Kawasaki; Mohd Zafri Baharuddin; Mohamad Zoinol Abidin Abd. Aziz; Mardina Abdullah; Vernon Cooray (Atmospheric Research, 2024)

Biodegradation of PVCs through in-vitro identification of Bacillus albus and computational pathway analysis of ABH enzyme - Muhammad Naveed; Rida Naveed; Tariq Aziz; Arooj Azeem; Mahrukh Afzal; Muhammad Waseem; Metab Alharbi; Abdulrahman Alshammari; Abdullah F. Alasmari; Thamer H. Albekairi (Biodegradation, 2024)

Kinetic exploration of CO2 methanation over nickel loaded on fibrous mesoporous silica nanoparticles (CHE-SM) - Muhammad Akmal Aziz; Aishah Abdul Jalil; Nurul Sahida Hassan; Mahadi Bin Bahari; Abdul Hakim Hatta; Tuan Amran Tuan Abdullah; Nurfatehah Wahyuny Che Jusoh; Herma Dina Setiabudi; Rajendran Saravanan (Process Safety and Environmental Protection, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

An Aedes–Anopheles Vaccine Candidate Supplemented with BCG Epitopes Against the Aedes and Anopheles Genera to Overcome Hypersensitivity to Mosquito Bites - Muhammad Naveed; Urooj Ali; Tariq Aziz; Rida Naveed; Sarmad Mahmood; Muhammad Mustajab Khan; Metab Alharbi; Thamer H. Albekairi; Abdullah F. Alasmari (Acta Parasitologica, 2024)

Integrated application of biochar and chemical fertilizers improves wheat (Triticum aestivum) productivity by enhancing soil microbial activities - Muhammad Abdullah Aziz; Khalid Saifullah Khan; Rabia Khalid; Muhammad Shabaan; Abdulaziz G. Alghamdi; Zafer Alasmary; Mosaed A. Majrashi (Plant and Soil, 2024)

Protecting coastal tourism through developing tourists' environment responsible behaviour - Sadia Aziz; Muhammad Abdullah Khan Niazi (Journal of Outdoor Recreation and Tourism, 2023)

Nutritional Value of Dry Fish in Bangladesh and Its Potential Contribution to Addressing Malnutrition: A Narrative Review - Md. Hasan Al Banna; Abdullah Al Zaber; Nahidur Rahman; Md Abrar Mozahid Siddique; Muhammad Abu Bakr Siddique; John Elvis Hagan; M. A. Rifat; Christiana Naa Atsreh Nsiah-Asamoah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Md Shafiqul Islam Khan (Fishes, 2022)
Understanding the linkage between the nutrient composition of foods and individuals’ recommended nutrient intake is important to address malnutrition. Despite it being a traditional and popular food item in Bangladesh, the nutrient composition of dry fish has not been reviewed yet. This study used a narrative review to assess the nutrient composition of dry fish and estimated its potential contribution to addressing some common nutritional deficiencies among children and pregnant and lactating women in Bangladesh. Records were collected from different databases, including the Web of Science, Google Scholar, PubMed, ScienceDirect, Banglajol, and ResearchGate. Data were extracted from 48 articles containing 1128 entries regarding nutrient composition. Most of the nutrient analyses estimated the proximate composition, whereas vitamin, mineral, amino acid, and fatty acid compositions were scarce in the literature. We found that dry fish has high protein and mineral content and could contribute highly to meeting the recommended nutrient intake of protein, iron, zinc, and calcium for children and pregnant and lactating women. The summarized nutrient composition data could be useful for further research to observe how dry fish could be best utilized to address malnutrition in Bangladesh. This narrative review recommends that further nutrient analysis, with emphasis on vitamin, mineral, and fatty acid compositions.

Pyroptosis in acute pancreatitis and its therapeutic regulation - Abdullah Al Mamun; Suzia Aktar Suchi; Md. Abdul Aziz; Muhammad Zaeem; Fahad Munir; Yanqing Wu; Jian Xiao (Apoptosis, 2022)

Organic geochemical and petrological evaluation to assess the remaining hydrocarbon potential and depositional conditions: a case study of the Paleozoic shales of west Perlis region, northern Peninsular Malaysia - Muhammad Nadzmi Abdul Ghofur; Jasmi Hafiz Abdul Aziz; Yousif M. Makeen; Wan Hasiah Abdullah; Mohammed Hail Hakimi (Arabian Journal of Geosciences, 2022)